JUNIOR HIGH SCHOOL TEACHER'S PERCEPTION ON IMPLEMENTATION OF EDUCATION FOR SUSTAINABLE DEVELOPMENT: A STUDY IN WEST JAVA PROVINCE - Dadi Mulyadi; Mohammad Ali; Eero Ropo; Laksmi Dewi (PEDAGOGIA, 2023)
Education for Sustainable Development (ESD) is a global program to provide students with knowledge, skills, attitudes, and values needed to address the challenges of sustainability. The condition of Indonesia's sustainable development index still faces challenges. Indonesia's average SDGs achievement index compared to other ASEAN countries is in position 7 out of 10 ASEAN countries in the 2017-2021 timeframe with an average of 64.3 out of a maximum score of 100. Education as a driving force for achieving a sustainable development index has not been used as an instrument to support achieving a better index. This study aims to describe the implementation of ESD in junior high school teachers in West Java. This study used a survei using questionnaires distributed to 384 teachers spread across five regencies/cities in West Java Province. Findings of the study show that 48,23% teachers do not know about ESD, have not implemented ESD 51,27%, and do not the competencies needed to implement ESD 48,57%. The findings imply in the necessity of relevance competencies to implement ESD.